Ocean-continent subduction cannot be initiated without preceding intra-oceanic subduction! - Koptev, Alexander; Cloetingh, Sierd; Gerya, Taras; Sternai, Pietro; Botsyun, Svetlana (Frontiers in Earth Science, 2022)
The formation of new subduction zones is a key element of plate tectonics and the Wilson cycle, and many different controlling mechanisms have been proposed to initiate subduction. Here, we provide a brief overview of the known scenarios of subduction initiation in intra-oceanic and ocean-continent tectonic settings. Intra-oceanic subduction is most commonly associated with mechanical heterogeneities within the oceanic lithosphere, such as pre-existing fracture zones, spreading ridges, and transform faults. Numerous and well-recognized examples of new active subduction zones formed in intra-oceanic environments during the Cenozoic, suggesting that the initiation of ocean-ocean subduction must be a routine process that occurs “easily and frequently” in the mode of plate tectonics currently operating on Earth. On the contrary, the most traditional mechanisms for the establishment of classic self-sustaining ocean-continent subduction – passive margin collapse and subduction transference – are surprisingly rare in observations and difficult to reproduce in numerical models. Two alternative scenarios – polarity reversal and lateral propagation-induced subduction initiation – are in contrast much better documented in nature and experimentally. However, switching of subduction polarity due to arc-continent collision and lateral transmission of subducting plate boundaries are both inextricably linked to pre-existing intra-oceanic convergence. We, therefore, conclude that the onset of classic ocean-continent subduction zones is possible only through the transition from a former intra-oceanic subduction system. Future closure of the Atlantic Ocean can be viewed as an archetypal example of the role of transitional process between intra-oceanic subduction and the development of new subduction zone at passive continental margin.